2021
DOI: 10.1109/tcsi.2021.3069168
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Operand Trimming Approximate Logarithmic Multiplier

Abstract: We present an approximate logarithmic multiplier with two-stage operand trimming, which prioritises area and energy consumption while retains acceptable accuracy. The multiplier trims the least significant parts of input operands in the first stage and the mantissas of the obtained operands' approximations in the second stage. We evaluated the multiplier's efficiency in terms of error, energy, and area utilisation using NanGate 45nm. The experimental results show that the proposed multiplier exhibits smaller a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…Multiplication is a very common, but expensive operation, with exact multipliers being large circuits that consume a significant amount of energy. Various approximate multipliers have been proposed in recent years [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Many studies reported that approximate multipliers behave well in neural network processing [ 56 , 59 , 60 , 61 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiplication is a very common, but expensive operation, with exact multipliers being large circuits that consume a significant amount of energy. Various approximate multipliers have been proposed in recent years [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Many studies reported that approximate multipliers behave well in neural network processing [ 56 , 59 , 60 , 61 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the approximate multiplier design, we balanced accuracy and energy efficiency to suit the application’s needs. Various approximate multipliers have been proposed in recent years [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Approximate multipliers follow one of three design strategies: the approximate logarithmic design, the approximate nonlogarithmic design, and the hybrid design.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations